Corneal clouding in GM1-generalized gangliosidosis. - Babarik, A. (1976)
Corneal clouding is added to the list of clinical and chemical abnormalities which occur both in GM1-generalized gangliosidosis and in Hurler's syndrome (and some other mucopolysaccharidoses). The parents of our patient were first cousin Yemeni and had partial beta-galactosidase deficiency in their leucocytes and cultured fibroblasts.